Vegetation Analysis of Open and Closed Canopy Sal and Miscellaneous forests of Satpura Plateau, India - Patra, A. K.; Pande, P. K.; Sahu, T. R. (Indian Forester, 2007)
Vegetation was analyzed quantitatively in miscellaneous open, miscellaneous closed, sal open and sal closed forests of West Chhindwara Forest Division (Madhya Pradesh). Total density for tree layer ranged between tree ha-1 1,650 (miscellaneous open) to 3,030 t ha-1 (sal closed); 4,960.23 (miscellaneous open) to 10,840 (sal closed) for shrubs and 3,180 (miscellaneous closed) to 3,18,000 (miscellaneous closed) plant ha-1 for herb layer, whereas the range for dominance (cm2 ha-1) was 1,65,855 (miscellaneous closed) to 16,38,325 (sal closed) for trees; 5428 (miscellaneous open) to 16,100 (sal closed) for shrubs and 14,778 (miscellaneous open) to 11,28,020 (sal open) for herbs. It is very interesting to note that density and dominance of trees are invariably higher in closed forests, whereas, shrubs and herbs are higher in open forests except shrubs for miscellaneous closed forest. Miscellaneous open forest showed highest species richness followed by miscellaneous closed, sal closed and sal open for tree species. Diversity index values were highest for miscellaneous open followed by miscellaneous closed, sal open and sal closed. Miscellaneous open also showed highest species richness values, while sal open and closed miscellaneous showed lowest values, respectively, for shrub and herb species. Sal open and sal closed showed lowest values, respectively, for shrub and herb species for diversity index. Invariably, concentration of dominance followed the reverse trend to species diversity. Miscellaneous open and miscellaneous closed were more similar sites for tree and shrub species, whereas sal open and closed showed more similarity while considering herbs as the measure. Miscellaneous closed and sal open were most dissimilar sites for trees and shrubs and miscellaneous and sal closed for herb species. Examination of disturbance magnitude indicated that openness of the stand does not disturb the regeneration and stand development in terms of total tree composition in miscellaneous forest, whereas, it disturb the composition of Shorea robusta in case of open sal stand in ecotone.